Prenatal diagnosis of a "living" oropharyngeal fetus in fetu: a case report - Ling Wang; Baiguo Long; Qichang Zhou; Shi Zeng (BMC, 2019)
Abstract Backgroud Fetus in fetu (FIF) is a rare malformation in which a parasitic twin within its more mature twin. Most of the FIF locate in the retroperitoneum and are acardiac and anencephalic. Case presentation Here, we describe a unique case of oropharyngeal fetus in fetu with a rudimentary two-chambered heart detected by prenatal ultrasonography. The parents terminated this pregnancy after counseling. Macroscopic examination found a solid mass between the oral and fetal chest, with a rudimentary two-chambered heart at the lowest part of the mass. Microscopic findings showed amniotic membrane, skin, cartilage, gastrointestinal and neural tissue. Conclusions Prenatal ultrasound can identify rudimentary organs suspecting FIF from early pregnancy. Detection of fetal heart beat facilitates differential diagnosis with teratomas, providing essential information for parental consulting and management.